Baseline differences in characteristics and risk behaviors among people who inject drugs by syringe exchange program modality: an analysis of the Miami IDEA syringe exchange - Siddharth Iyengar; Adam Kravietz; Tyler S. Bartholomew; David Forrest; Hansel E. Tookes (BMC, 2019)
Abstract Background In March of 2016, Florida passed the Infection Disease Elimination Act (IDEA), legalizing the formation of the first syringe exchange program in Florida, which opened in December of 2016 at a fixed site in Overtown, Miami. Since that time, the exchange expanded in April of 2017 to include a mobile van unit that provides the same services at different locations throughout Miami-Dade County. Methods Trained interviewers conducted face-to-face interviews from all first-time participants at the IDEA Exchange, both at the fixed site and the mobile van unit. Results Among 718 first-time enrollees, 74.8% were male, 52.1% were non-Hispanic White, 85.9% completed high school, 59.8% were unemployed, 42.1% were homeless, 54.2% reported an annual income of less than $15,000, and the mean age was 38 years. Participants at the fixed site and mobile van unit reported differences in socioeconomic status, injection drug-related behaviors, and pre-existing hepatitis C virus (HCV) infection status. Conclusions Taken together, these results suggest that the mobile unit is capturing a subset of PWID in Miami that the fixed site is not, and vice-versa. As the opioid crisis extends into all demographics, such multimodal efforts to target various populations of PWID should be kept in mind, especially when unveiling future syringe exchanges in Florida and other late-adopting states.